2016
DOI: 10.1371/journal.pone.0151524
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Different Ploidy Saccharum spontaneum Based on rDNA-ITS Sequences

Abstract: Saccharum spontaneum L. is a crucial wild parent of modern sugarcane cultivars whose ploidy clones have been utilized successfully in improving the stress resistance and yield related traits of sugarcane cultivars. To establish knowledge regarding the genetic variances and evolutional relationships of ploidy clones of Saccharum spontaneum collected in China, the rDNA-ITS sequences of 62 ploidy clones including octaploid clones (2n = 64), nonaploid clones (2n = 72), decaploid clones (2n = 80), and dodecaploid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Due to its large ecogeographical distribution, S . spontaneum is considered the most diverse species in the Saccharum genus [ 67 , 68 ]. This species presented the highest number of alleles across the 12 microsatellite loci.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its large ecogeographical distribution, S . spontaneum is considered the most diverse species in the Saccharum genus [ 67 , 68 ]. This species presented the highest number of alleles across the 12 microsatellite loci.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al analyzed differences among nrDNA-ITS sequences from 62 different multiple S . spontaneum materials and showed that 4 species had high variation, especially the nonuploid and decaploid population [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies on nrDNA-ITS in sugarcane germplasms, the tetra-primer ARMS PCR technique can be used to analyze genetic diversity and phylogenetic relationships in interspecific and intergenus samples [ 9 , 10 , 19 ]. However, studies exploring the identification and use of SNPs as molecular markers in Saccharum breeding have not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…officinarum were clustered together based on 45S rDNA-ITS haplotype data in S . spontaneum [ 3 ]. Pan et al found that the two S .…”
Section: Discussionmentioning
confidence: 99%
“…However, the taxonomy within the genus Saccharum remains controversial. Over the past two decades, molecular cytogenetics and markers have contributed to inference of the phylogenetic relationship of the species within the genus Saccharum [ 3 – 7 ], and therefore the classification of the species within this genus has gradually been elucidated. The currently accepted taxonomy for the genus Saccharum comprises six species, including Saccharum officinarum , Saccharum robustum , Saccharum spontaneum , Saccharum sinense , Saccharum barberi , and Saccharum edule [ 8 ].…”
Section: Introductionmentioning
confidence: 99%